Keselamatan sebagai Partisipasi dalam Kehidupan Ilahi: Telaah Eskatologis dalam Teologi Katolik Kontemporer - Sergius Lay; Maria Winar Hati Waoma; Monika Simpati Gea; Enisa Bulolo; Ripka Eklesia Harianja; Emerensia Werihati Ndruru (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the meaning of salvation from an eschatological perspective within the framework of Catholic theology. Catholic eschatology is not merely understood as a discussion of end-time events but also as a reflection on the ultimate fulfillment of human life in relationship with God. Using a systematic theological method and a hermeneutical approach to various documents of the Catholic Church’s Magisterium, this research analyzes salvation as human participation in divine life, which begins in the present life and reaches its fullness in eternal life. The study focuses on three main aspects: salvation as active human participation in God's saving work; Catholic eschatological elements, including death, judgment, purgatory, heaven, and hell as stages in the fulfillment of salvation; and the communal and cosmic dimensions of salvation that encompass all humanity and creation. The findings indicate that salvation in Catholic theology possesses a dynamic and holistic eschatological character. Salvation is not only a future reality but is already present in the lives of believers through faith, grace, and communion with Christ. Therefore, the hope of final salvation encourages believers to live in love, moral responsibility, and openness to God's work in the world.